Donations, risk attitudes and time preferences: A study on a ltruism in primary school children - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
We study in a sample of 1,070 primary school children, aged seven to eleven years, how altruism in a donation experiment is related to children's risk attitudes and intertemporal choices. Examining such a relationship is motivated by theories of reciprocal altruism that provide a cornerstone for understanding human social behavior. We find that higher risk tolerance and patience in intertemporal choice increase, in general, the level of donations, albeit the effects are non-linear. We confirm earlier results that altruism increases with age during childhood and that girls are more altruistic than boys. Having older brothers makes subjects less altruistic.
Keywords: C91; D03; D63; D64; 330; altruism; donations; risk attitudes; intertemporal choices; experiment; children